Long-term exposure to chemicals in sewage sludge fertilizer alters liver lipid content in females and cancer marker expression in males. (March 2019) - Filis, Panagiotis; Walker, Natasha; Robertson, Linda; Eaton-Turner, Emily; Ramona, Lauma; Bellingham, Michelle; Amezaga, Maria R.; Zhang, Zulin; Mandon-Pepin, Beatrice; Evans, Neil P.; Sharpe, Richard M.; Cotinot, Corinne; et al.
Abstract: Background: The increased incidence of diseases, including metabolic syndrome and infertility, may be related to exposure to the mixture of chemicals, which are ubiquitous in the modern environment (environmental chemicals, ECs). Xeno-detoxification occurs within the liver which is also the source of many plasma proteins and growth factors and plays an important role in the regulation of homeostasis. Objectives: The objective of this study was to investigate the effects of ECs on aspects of liver function, in a well characterized ovine model of exposure to a real-life EC mixture. Methods: Four groups of sheep ( n = 10–12/sex/treatment) were maintained long-term on control or sewage sludge-fertilized pastures: from conception to culling at 19 months of age in females and from conception to 7 months of age and thereafter in control plots until culling at 19 months of age in males. Environmental chemicals were measured in sheep livers and RNA and protein extracts were assessed for exposure markers. Liver proteins were resolved using 2D differential in-gel electrophoresis and differentially expressed protein spots were identified by liquid chromatography/tandem mass spectroscopy. Results: Higher levels of polycyclic aromatic hydrocarbons (PAHs) and lower levels of polychlorinated biphenyls (PCBs) in the livers of control males compared to control females indicated sexually dimorphic EC body burdens. Increased levels of the PAHs Benzo[ a ]anthracene and chrysene and reduced levels of PCB 153 and PCB 180 were observed in the livers of continuously exposed females. EC exposure affected xenobiotic and detoxification responses and the liver proteome in both sexes and included major plasma-secreted and blood proteins, and metabolic enzymes whose pathway analysis predicted dysregulation of cancer-related pathways and altered lipid dynamics. The latter were confirmed by a reduction in total lipids in female livers and up-regulation of cancer-related transcript markers in male livers respectively by sewage sludge exposure. Conclusions: Our results demonstrate that chronic exposure to ECs causes major physiological changes in the liver, likely to affect multiple systems in the body and which may predispose individuals to increased disease risks. Highlights: Chronic exposure to environmental chemicals affects liver physiology. Proteomic measurements showed widespread dysregulation in the exposed livers. Exposure dysregulated important plasma proteins such as albumin and transferrin Reduction in total lipids in the exposed female livers Increase in cancer markers in the exposed male livers